Psychological effects of horizontal price display: how left-right location shapes reference price and perceived quality - Park, Eun Young; Jang, Jung Min (Frontiers in Psychology, 2025)
This study examines the impact of display locations of regular and sale prices on reference price estimation, drawing on anchoring and adjustment theory and the left-to-right directionality in reading habits. It focuses on how the spatial positioning of the regular price relative to the discount price affects perceived quality and subsequently shapes reference price judgments. Conducted across both offline and online settings using varied product stimuli, three laboratory studies using comparative price advertisements that presented both prices on the same page consistently demonstrate that placing the regular price to the left of the discount price results in higher reference price estimations. The findings also confirmed that perceived product quality mediates the proposed effect. This research offers new insights into how the spatial placement of pricing information significantly affects consumer perception and decision-making, contributing to consumer psychology.